Effects of supplementary concentrates and voluntary forage intake on grazing cattle in pastures of Cynodon plectostachyus in a semi-tropical region of Mexico - LÓPEZ-GONZÁLEZ, FELIPE; VALDÉS, JAIR JESÚS SÁNCHEZ; YONG-ÁNGEL, GILBERTO; CASTELÁN-ORTEGA, OCTAVIO ALONSO; ESTRADA-FLORES, JULIETA GERTRUDIS (The Indian Journal of Animal Sciences, 2021)
The objective of the present study was to evaluate the effects of different levels of concentrate on the productive response of grazing dairy cattle and to determine voluntary forage intake. The experiment was carried out in a 4×4 Latin square design repeated three times, in which different inclusion levels of experimental concentrate were evaluated (EC) vs commercial concentrate (CC). The treatments were as follows: EC1= 7.12 kg DM of EC + grazing, EC2=6.23 kg DM of EC+ grazing, EC3=5.34 kg DM of EC+ grazing, CC=7.12 DM kg of a commonly used commercial concentrate (CC), and free-access grazing. The voluntary intake was determinate throw n-alkanes technique. The variables evaluated in cattle were milk output, live weight, and body condition; milk samples were also taken to determine protein and fat contents. Net herbage accumulation (NHA), forage height, neutral detergent fiber (NDF), acid detergent fiber (ADF), digestibility of organic matter (DIVMO), and metabolizable energy (ME) of pasture grasses were evaluated in addition to voluntary intake and production costs. Significant differences in crude protein content were found between the evaluation periods but were not found for NDF, ADF, DIVMO, NHA, and ME. Significant differences were not found in voluntary intake but were present in total intake. The evaluated treatments did not differ with respect to animal response. Finally, significant differences were found in milk output. Greater milk production was obtained in treatments 1 and 2 (14.92 and 14.50 kg/day/animal, respectively.